2022
DOI: 10.1007/s00018-022-04620-8
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/planar cell polarity signaling controls morphogenetic movements of gastrulation and neural tube closure

Abstract: Gastrulation and neurulation are successive morphogenetic processes that play key roles in shaping the basic embryonic body plan. Importantly, they operate through common cellular and molecular mechanisms to set up the three spatially organized germ layers and to close the neural tube. During gastrulation and neurulation, convergent extension movements driven by cell intercalation and oriented cell division generate major forces to narrow the germ layers along the mediolateral axis and elongate the embryo in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 184 publications
(231 reference statements)
0
10
0
2
Order By: Relevance
“…Global gene expression data in MAP3K1-competent and -deficient epithelial cells has shown that MAP3K1 deficiency prevents the optimal activation of not only the canonical, but also the non-canonical WNT pathways. Non-canonical WNT signaling is a key regulator for the establishment of cell polarity in positional cell movement, morphogenesis and ductal organ formation ( Karner et al, 2006 ; Shi, 2022 ; Sugimura and Li, 2010 ). In line with the pathway analyses data, we found that MAP3K1 deficiency reduces acetylated α-tubulin, a fundamental marker for cell polarization, in the apical surface of the MD epithelium ( Andrew and Ewald, 2010 ; Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Global gene expression data in MAP3K1-competent and -deficient epithelial cells has shown that MAP3K1 deficiency prevents the optimal activation of not only the canonical, but also the non-canonical WNT pathways. Non-canonical WNT signaling is a key regulator for the establishment of cell polarity in positional cell movement, morphogenesis and ductal organ formation ( Karner et al, 2006 ; Shi, 2022 ; Sugimura and Li, 2010 ). In line with the pathway analyses data, we found that MAP3K1 deficiency reduces acetylated α-tubulin, a fundamental marker for cell polarization, in the apical surface of the MD epithelium ( Andrew and Ewald, 2010 ; Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These noncanonical Wnt signaling pathways are independent of β-catenin in their conduction process. 33 2.1. Wnt/β-Catenin Pathway.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Noncanonical Wnt signaling pathways include Wnt/Ca 2+ , which regulates calcium in cells, Wnt/planar cell polarity (PCP), and Wnt/ROR2. These noncanonical Wnt signaling pathways are independent of β-catenin in their conduction process …”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…This process is in part regulated by Wnt/PCP pathway, and disruptions in the regulation of this pathway caused by a mutation in wnt11f2 in zebrafish cause defects in the mediolateral cell intercalation, the migration of hypoblast cells, the cell division orientation, and in cell adhesion. 15–17 , 21 , 22 …”
Section: Wnt11f2 During Gastrulationmentioning
confidence: 99%